Análise de conceito e validação de conteúdo de risco de lesão do trato urinário : proposta de diagnóstico de enfermagem - Garbuio, Danielle Cristina (Universidade Federal de São Carlos, 2012)
The catheterization is a procedure common in hospitalized patients, which are mostly performed by professional nurses. However, it´s not a risk-free procedure, and for this reason, is necessary that the nurse, know the risk factors that may lead to a possible injury to the urinary tract. Considering the difficulty in selecting a nursing diagnosis that addresses fully the risk of patients using these catheters the aim of this study was to develop, propose and validate risk of injury to the urinary tract as a nursing diagnosis. The methodological approach was divided into three stages: concept analysis of urinary tract injury, preparation of the proposed nursing diagnosis and validation of this proposal by a group of experts. The concept analysis was developed using the Evolutionary Method of Rodgers. A search in the databases LILACS, The Cochrane Library, CINAHL and PubMed was performed by combining descriptors controlled and uncontrolled. The final sample was composed of 21 selected articles and a book chapter. Each text was read in its entirety first and then looking for attributes of the concept, related concepts, terms and substitutes contextual bases interdisciplinary, socio-cultural antecedents and consequences. The findings of this analysis were organized to prepare the elements of nursing diagnosis proposed, considering the seven axes of NANDA´s Taxonomy II. These elements were organized in an instrument that was sent to experts for content validation diagnosis. The concept analysis found that urinary tract injury is a term used in reference to damages, whether traumatic, inflammatory or infectious, affecting the lower urinary system as a result of an injury that can be attributed to several factors, but mainly the urinary catheters. The major complications identified through the attributes of the concept were: urinary tract infection, false passage, pain, urethral fistula, stricture, inability or difficulty urinating, mucosal irritation, bladder and urethral erosion, laceration of the canal, bladder and urethra , tissue necrosis and bladder spasms. The main risk factors identified from the background to the concept were: advanced age, urologic variations, latex allergy, constipation, inadequate fluid intake, obesity, anatomic variations of the pelvic organs, cognitive impairment, confusion, sedation, detrusor-sphincter dyssynergia, spinal cord injury, long time of bladder catheterization, catheter poorly lubricated at the time of insertion, lack of care in handling the catheter, difficulty inserting and removing the catheter, catheter obstruction, catheter size and material , overfilled balloon retention, collection bag with volume above the stated limit, fixing incorrect or missing, repeated and frequent catheterizations. On this basis the proposal diagnostic was Risk of urinary tract injury. These data were submitted in the form of an instrument with a four-point Likert scale for the assessment of experts and it was evaluated by 16 experts. The insertion of the proposed diagnosis was validated in Domain 11 and Class 2 of NANDA´s Taxonomy II. The label was validated as Risk of urinary tract injury and the definition was validated with some changes. The validated risk factors were: age, latex allergy, obesity, pelvic organ anatomical variations, cognitive impairment, detrusor-sphincter dyssynergia, spinal cord injury, mental confusion, poor knowledge of the patient or caregiver about urinary catheter care, long-term use of catheters bladder, the need to use retention balloon inflated with 30ml or more need to use urinary catheter large caliber, impossibility of fixing the urinary catheter, repeated and frequent catheterizations. These results contribute to increase the quality of nursing work.
Concept analysis and content validation of risk of injury to the urinary tract: proposed nursing diagnosis
Keywords: Enfermagem; Diagnóstico de enfermagem; Estudos de validação; Cateteres; Sistema urinário; Nursing diagnosis; Validation studies; Catheters; Urinary tract; CIENCIAS DA SAUDE::ENFERMAGEM